Analysis of Insulation Resistance Testing During Biennial Maintenance of 20 kV Incoming Cubicle Circuit Breakers at Gunung Megang Substation, PT PLN (Persero) ULTG Prabumulih UPT Baturaja - Pratama, Muhammad Rizky; Wibowo, Pristisal; Tarigani, Adisastra Pengalaman (Fidelity : Jurnal Teknik Elektro, 2025)
This report aims to see the value of insulation resistance on the power breaker that will be tested. The test method uses Megger MIT1025 test equipment where the test performed is Insulation Resistance Testing. The tests carried out can determine the value of insulation resistance on the equipment to be tested is still classified as in good condition or not. The average test result value is in the amount of Giga so that it can be declared in good condition. The value still meets the allowable standards according to SK-DIR 0520 , so that the incoming cubicle power breaker 20 kV GI Gunung Megang is still suitable for use.